2011
DOI: 10.3109/0886022x.2011.615965
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Icodextrin versus Glucose Containing Peritoneal Dialysis in Metabolic Management of Peritoneal Dialysis Patients

Abstract: Objectives: The objective of this article is to study the available works on comparison between icodextrin-based solutions (ICO) and glucose-based solutions (GLU) in peritoneal dialysis (PD) patients. The final aim was to get evidence for potential differences in metabolic management of PD patients by comparing the ICO with the GLU for the long dwell once a day. Methods: A meta-analysis of included reports, identified by MEDLINE and other sources, containing information on fasting plasma glucose, total cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The timing of blood collection for the measurement of fasting glucose (PD fluids drained out or dwelled) and the dwell times were inconsistent across the participants. Unfortunately, this is a common limitation of studies on MS in PD patients (47).…”
Section: Discussionmentioning
confidence: 99%
“…The timing of blood collection for the measurement of fasting glucose (PD fluids drained out or dwelled) and the dwell times were inconsistent across the participants. Unfortunately, this is a common limitation of studies on MS in PD patients (47).…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews of randomized controlled trials (RCTs) have compared icodextrin-containing to glucose-only PD regimens. [40][41][42] However, their estimates of important outcomes such as mortality risk and hospitalization, as well as systemic metabolism and peritoneal function, have wide confidence intervals (CIs). This uncertainty may have arisen because of nonincluded evidence, such as unpublished data from published studies, studies published in non-English languages, and studies that have undergone regulatory as opposed to academic peer review.…”
mentioning
confidence: 99%
“…Various systematic reviews have shown variable results on the impact of icodextrin on peritoneal transport status or peritoneal creatinine clearance. Earlier meta‐analyses by Qi et al 65 and He et al 76 suggested that icodextrin improved small solute clearance; however, more recent meta‐analyses did not show any effect of icodextrin on peritoneal solute transport rate or peritoneal small solute clearance 66,67 …”
Section: Osmotic Agentmentioning
confidence: 99%